SISTEM INFORMASI PERPUSTAKAAN BERBASIS WEB DI SMP BOPKRI 5 KEDUNG PENJALIN JEPARA - Isabela, Putri Cintia; Setianti, Novita; Sulistyasni, Sulisyasni (Jurnal Teknologi Informasi, Ilmu Komputer dan Manajemen, 2024)
School libraries play an important role in supporting the teaching and learning process by providing various information resources. However, manual library management at SMP BOPKRI 5 Kedung Penjalin, Jepara, often faces challenges such as errors in recording, data management, and report generation. To address these issues, a web-based library information system was developed with the aim of improving efficiency and accuracy in library management. The system was developed using the Waterfall method, with testing conducted through two approaches: Black Box Testing and the System Usability Scale (SUS). The results of the Black Box testing showed that all features functioned according to the specifications. Meanwhile, SUS testing, involving 12 respondents from the school staff, yielded an average score of 79.4, categorized as "Good" and "Acceptable. "The findings of this study demonstrate that the developed system successfully improves library management efficiency, minimizes errors in record-keeping, and facilitates easier access to information while increasing user satisfaction. Library Information System, Web, Black Box Testing, System Usability Scale (SUS).